2002
DOI: 10.1029/2000jc000466
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of data sets used to force sea ice models in the Arctic Ocean

Abstract: [1] Basin-scale sea ice models are often run uncoupled to either an atmosphere or ocean model to evaluate the sea ice model, to compare different models, and to test changes in physical parameterizations. Such simulations require that the boundary forcing be specified. The specification of atmospheric forcing associated with the surface heat and freshwater fluxes has been done in various sea ice simulations using climatology, numerical weather prediction analyses, or and satellite data. However, the errors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…For one, reanalysis output is sometimes used to force large-scale or local sea ice and ocean models to evaluate their performance against available observations (e.g., Brodeau et al, 2010;Miller et al, 2007). Curry et al (2002) evaluated several data sets used to force sea ice models during the SHEBA time period and noted that substantial differences can be found between the different data sets. Our evaluation results in a similar conclusion, with notable differences between products in quantities relevant to ocean processes and sea ice growth and decay, such as winds, precipitation and radiation.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For one, reanalysis output is sometimes used to force large-scale or local sea ice and ocean models to evaluate their performance against available observations (e.g., Brodeau et al, 2010;Miller et al, 2007). Curry et al (2002) evaluated several data sets used to force sea ice models during the SHEBA time period and noted that substantial differences can be found between the different data sets. Our evaluation results in a similar conclusion, with notable differences between products in quantities relevant to ocean processes and sea ice growth and decay, such as winds, precipitation and radiation.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The atmospheric forcing set is the National Centers for Environmental PredictionNational Center for Atmospheric Research (NCEP-NCAR) 40-Year Reanalysis Project global dataset (Kalnay et al 1996). This forcing set was chosen for its good overall performance for surface-level processes in the Arctic (Jakobson et al 2012), although the radiative fluxes have been shown to be too high because of poor representation of the cloud fraction (Curry et al 2002;Zib et al 2012). For the Antarctic the data also perform well at surface levels, although there is a bias for too cold air temperatures in the western Antarctic (Yu et al 2010) and radiative fluxes that are too high (Vancoppenolle AUGUST 2015 W…”
Section: A Standard Run Configurationmentioning
confidence: 99%
“…Retrieval of atmospheric variables from remote sensing data is hampered in the Arctic due to the high cloud coverage and difficulties in distinguishing the signals originating from the atmosphere and ice/snow surface. The atmospheric model forecasts, analyses, and re-analyses include large errors, in particular in the near-surface wind, air temperature, air humidity, precipitation, as well as the radiative and turbulent surface fluxes [Curry et al, 2002;Tjernström et al, 2005]. Unfortunately, these are the meteorological variables that most directly control the sea ice growth, melt and drift.…”
Section: Introductionmentioning
confidence: 99%